Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) Menggunakan Macromedia Flash 8 Dalam Pembelajaran IPA Fisika Siswa Di Kelas VIII MTsN Tarusan - Sari, Milya (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2017)
This study aims to determine whether the results of learning physics by using a type of cooperative learning model Think Talk Write higher than conventional learning in class VIII MTsN Tarusan. This research is quasy experiment with the design study is a randomized control group only design. The study population was a class VIII MTsN Tarusan Academic Year 2015/2016 second semester consisting of 4 classes. To take samples in this study used cluster random sampling technique. Based on the results of the sample selection, diperolehlah VIIID class as an experimental class and the class as a class VIIIB control. Data collection techniques used include tests and observation. The data analysis technique used to test the hypothesis is by using the t test for normally distributed data and data group has a homogeneous variance. Based on analysis of data obtained, the student activity (affective aspect) in the experimental class is higher than the control class. Affective Aspects students Meninggkakatnya effect on the cognitive learning outcomes. Where the average student learning outcomes in experimental class is 72,4 while the control group was 62,5